Implementation of Fiscal Incentive Policy for Ease of Investment in the Singkawang City Government - Rikky, Rikky; Deliarnoor, Nandang Alamsah; Bintari, Antik (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study highlights the implementation of fiscal incentive policies for the ease of investment in Singkawang City. This study analyze the factors that influence the success of policy implementation using dimensions which are expressed by Grindle by analyzing variables about the contents of the policy and the context of implementation. This study selects a qualitative method because it allows researchers to understand social phenomena in its context more comprehensively. Researchers collected data through three main techniques: interviews, observations, and documentation. This study chose to apply data analysis techniques consisting of three main steps, namely data reduction, data presentation, and drawing conclusions. The results showed that the implementation of fiscal incentive policies for the ease of investment in the Singkawang City Government in the span of 2023-2024 was not yet optimal. Weaknesses both in policy content and from the context of their implementation are identified.